2009
DOI: 10.1016/j.jcmg.2009.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Prognostic Value of Gated Rb-82 Positron Emission Tomography Myocardial Perfusion Imaging Over Clinical Variables and Rest LVEF

Abstract: OBJECTIVES This investigation sought to study the incremental value of gated rubidium (Rb)-82 positron emission tomography (PET) myocardial perfusion imaging (MPI) over clinical variables for predicting survival and future cardiac events. BACKGROUND The prognostic value of Rb-82 PET-MPI and left ventricular ejection fraction (LVEF) reserve (stress minus rest LVEF) is not well defined. METHODS 1,432 consecutive patients undergoing gated rest/vasodilator stress rubidium-82 PET were followed up for at least 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(140 citation statements)
references
References 15 publications
9
127
1
3
Order By: Relevance
“…18 The present study supports the notion that an improvement in LVEF is likely preceded by a reduction in LVAS or 'synchrony reserve'. Studies have shown EF reserve to be inversely related to the severity of ischemia or infarction.…”
Section: See Related Article Pp 43-52supporting
confidence: 88%
See 1 more Smart Citation
“…18 The present study supports the notion that an improvement in LVEF is likely preceded by a reduction in LVAS or 'synchrony reserve'. Studies have shown EF reserve to be inversely related to the severity of ischemia or infarction.…”
Section: See Related Article Pp 43-52supporting
confidence: 88%
“…Studies have shown EF reserve to be inversely related to the severity of ischemia or infarction. 12,19 Contrary to the systematic evaluation LVEF reserve and its prognostic value, 18 the presence of a synchrony reserve is hypothetical and its clinical value is unknown. A prospective and more structured evaluation of LVAS in patients with CAD will be needed to determine whether it has a diagnostic and prognostic role in patient management when global LV function is relatively preserved.…”
Section: See Related Article Pp 43-52mentioning
confidence: 99%
“…PET images provide incremental prognostic information to the clinical and angiographic findings with regard to event-free survival. An increased extent and severity of perfusion defects with stress PET were reported to be associated with increased frequency of adverse cardiac events, thus, this indicates PET can be used to predict cardiac mortality [41,42].…”
Section: Journal Ofmentioning
confidence: 95%
“…An LVEF reserve \0%, indicating a drop in LVEF with stress, has diagnostic and prognostic significance and can be optionally reported. 38 SPECT and PET MPI also allow interpretation of the perfusion, size, and global and segmental function of the right ventricle (RV). Data elements for this assessment are provided in Table 16.…”
Section: Study Descriptionmentioning
confidence: 99%